PENGUATAN PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN ILMU ALAMIAH DASAR - Wicaksono, Anggit Grahito (UNIVERSITAS SLAMET RIYADI, 2016)
Some problems which are quite alarming from the world of education in Indonesia is acase of deviant behavior and moral learners that do not conform with the values of thecharacters as well as the scientific attitude itself, including bullying. Strengthening charactereducation in learning is needed, both the material and the learning process. Charactereducation has a close connection with a scientific attitude so that subjects basic natural sciencecan contribute in strengthening character education. Strengthening character education throughlearning basic natural science can be done by applying the model or approach to learning inaccordance with the nature of science include: inquiry approach, contextual approach, theapproach process skills, and scientific approach.Keywords: Character Building, Science Learning, Basic Natural Sciences